Fotojornalismo maranhense: carreira, trajetória e desafios na rotina dos profissionais - BARROS, Rosana Ferreira (2023)
Our starting point is the transformation scenario of Journalism and the crisis that affects professional values and identities from which this dissertation seeks to understand how these changes directly impact the photojournalist. The research question is: What is it like to be a photojournalist today in Maranhão, considering the two largest cities in the state? The main objective of the research was to understand the scenario of photojournalism in Maranhão from the perspective of the professional and the meaning of being a photojournalist in the context of media convergence and digital technologies. The specific objectives aim to know how the professional understands his profession and the changes taking place, identify the different areas of activity of the photojournalist from Maranhão, and understand how photojournalists adapt to changes in the profession. Due to its methodology, this research is characterized as empirical with a qualitative approach, in which semi-structured interviews (DUARTE, 2009; LIMA, 2016) were carried out with photojournalists in the cities of Imperatriz and São Luís. A total of 18 people with different profiles selected through the snowball technique (VINUTO, 2014; ALONSO, 2016) were interviewed. The interviews were carried out between July 16 and October 26, 2021, in person and online through the Google Meet platform, lasting between thirty minutes and three hours each. Conceptually, the dissertation addresses the Crisis of Journalism and Convergence, highlighting the consequences of these changes for photojournalism. It also aims to build the narrative of the arrival of photography and the transformations of photojournalism in Maranhão in the cities of Imperatriz and São Luís. The investigation from the perspective of photojournalists about what their career means in contemporary times encompassed five categories created from their insertion in the field: who are the professionals interviewed and how they started their careers; how the productive routine was and is; how professionals face technology and social networks; if they consider photojournalism a sexist profession; and, finally, if they believe that the profession is going through a crisis or a remodeling. This way, the research intends to contribute to the debate around how photojournalism in Maranhão developed in the cities of São Luís and Imperatriz and to improve discussions on the subject at the national level.